Antifungal Treatment for Japanese Patients with Chronic Pulmonary Aspergillosis - Takahiro Takazono; Yoshiyuki Saito; Masato Tashiro; Masataka Yoshida; Kazuaki Takeda; Shotaro Ide; Naoki Iwanaga; Naoki Hosogaya; Noriho Sakamoto; Hiroshi Mukae; Koichi Izumikawa (Infectious Diseases and Therapy)
Abstract Introduction Despite the ongoing efforts to refine treatment durations and methods for patients with chronic pulmonary aspergillosis, the clinical use of antifungal agents remains unclear. This study aimed to describe the treatment practices, trajectories, and prognoses of newly diagnosed patients with chronic pulmonary aspergillosis. Methods Data from a longitudinal database from hospitals in Japan was used. The target population included patients who started antifungal treatment following their initial diagnosis of pulmonary aspergillosis, pulmonary aspergilloma, or chronic necrotizing pulmonary aspergillosis between October 2015 and September 2017. We described patient characteristics and treatment practices. Results Of the 680 patients analyzed, 253 (37.2%), 231 (34.0%), 155 (22.8%), 31 (4.6%), and 10 (1.5%) patients received the initial treatment with voriconazole, itraconazole, micafungin, caspofungin, and liposomal amphotericin B, respectively. Over 50% of the patients initially treated with micafungin or caspofungin switched to azoles within a month. Of the patients treated with antifungal agents, only 46.8% continued treatment for 6 months, indicating a lower retention rate. The overall mortality rate at 1 year was 24.7%. The median treatment duration of initial treatment until switching was 83 days (interquartile range [IQR], 159) for voriconazole and 162 days (IQR, 310) for itraconazole, indicating a significant variation in treatment duration. Notably, 15.7% (76/484) of the patients underwent a treatment switch between voriconazole and itraconazole in the initial azole treatment group. Conclusions Our findings highlight the challenges associated with sustaining long-term antifungal treatment.